Isolation and structures of virescenosides from the marine-derived fungus Acremonium striatisporum. (March 2016) - Afiyatullov, Shamil Sh.; Kalinovsky, Anatoly I.; Antonov, Alexandr S.; Zhuravleva, Olesya I.; Khudyakova, Yuliya V.; Aminin, Dmitry L.; Yurchenko, Anton N.; Pivkin, Mikhail V.
Graphical abstract: Highlights: Four new virescenosides were isolated from marine fungus Acremonium striatisporum . Structures of metabolites were elucidated by 1D, 2D NMR and MS. All compounds were examined for inhibition of non-specific esterase activity. Abstract: Four new diterpene glycosides, virescenosides R1 (1 ), R2 (2 ), R3 (3) and Z (4 ) were isolated from a marine strain of Acremonium striatisporum KMM 4401 associated with the holothurian Eupentacta fraudatrix . Structures of1–3 were determined as the corresponding biosides having isopimaradiene-type aglycons with additional oxidation and unsaturation patterns. Virescenosides Z (4 ) was structurally identified as altroside, containing 7-en-6-one group in the tricyclic aglycon moiety. The compounds1–4 were examined for inhibition of non-specific esterase activity in mouse lymphocytes.